Boron Nitride Nanoplatelets as a Solid Radical Initiator for the Aerobic Oxidation of Thiophenol to Diphenyldisulfide. Issue 5 (21st January 2015) - Dhakshinamoorthy, Amarajothi; Primo, Ana; Esteve‐Adell, Ivan; Alvaro, Mercedes; Garcia, Hermenegildo
Abstract Boron nitride (BN) nanoplatelets suspended in ethanol were obtained through the sonication of BN powders prepared through biopolymer‐templated pyrolysis and air calcination of (NH4)3BO3–chitosan powders. AFM measurements indicate that BN nanoplatelets have an average height of 1.5 nm and length and width dimensions between 30 and 100 nm. BN nanoplatelets exhibit higher catalytic activity for the molecular oxygen‐mediated oxidation of aromatic thiols to the corresponding disulfides than do boron and nitrogen‐codoped graphene or commercial bulk hexagonal BN. The reaction scope includes substituted aromatic and heteroaromatic thiols, whereas aliphatic thiols are considerably less reactive. The hot filtration test and radical quenching by N‐tert‐butyl‐α‐phenylnitrone support an autoxidation mechanism involving thiyl radicals. BN nanoplatelets are deactivated during the course of the reaction owing to aggregation. The present study uncovers the activity of BN nanoplatelets used as an insoluble radical initiator of SH bonds.